Green Tea Extract Increases the Number of Granulosa Cells and E2 Serum Levels of Female Rats Exposed by Cypermethrin - Fitria Jannatul Laili; Sri Winarsih; Karyono Mintaroem (Humanistic Network for Science and Technology (HNST), 2018)
1(CA), 2, 3 1(CA), Indonesia; (Corresponding Author) 2, Indonesia 4, Indonesia ABSTRACT Green tea extract (GTE), Camellia sinensis, known as a very effective antioxidant to repair the damage of organs exposed by stress oxidative. Cypermethrin (CYP) is a harmful substance that can accumulate in the body and cause oxidative stress. This study aimed to demonstrate the effect of GTE in increasing the number of granulosa cells and E2 serum levels. Female rats (Rattus norvegicus) were randomly selected and divided into 5 groups, control group (KN), a group given only CYP 20 mg/kg body weight/day (KP), groups given CYP 20 mg/kg body weight/day and then treated with GTE 7, 14, 28 mg/kg body weight/day (P1, P2, and P3 respectively). Treatment was given for 28 days. The number of granulosa cells was counted by HSel software, E2 serum levels were determined via ELISA ASSAY. Treatment results with GTE 7, 14, and 28 mg/kg body weight/day significantly (p < 0.05) increased the number of granulosa cells and E2 serum levels relative to KN. Administration of GTE 28 mg/kg body weight/day caused the greatest increase in the number of granulosa cells and E2 serum levels. Our result suggests that GTE has potential prevention to stress oxidative by CYP exposure in granulosa cells and E2 serum. Keywords: Cypermethrin, E2, Granulosa Cells, Green tea